2019
DOI: 10.3389/fbuil.2019.00082
|View full text |Cite
|
Sign up to set email alerts
|

Augmented Reality for Enabling Smart Nuclear Infrastructure

Abstract: This work presents a novel, comprehensive framework that leverages emerging augmented reality headset technology to enable smart nuclear industrial infrastructure that a human can easily interact with to improve their performance in terms of safety, security, and productivity. Nuclear industrial operations require some of the most complicated infrastructure that must be managed today. Nuclear infrastructure and their associated industrial operations typically features stringent requirements associated with sei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…The UI is controlled by hand gestures and voice commands making the application more intuitive and immersive. This application has been successfully demonstrated in a smart inspection of a nuclear facility in previous research by the same authors Mascaren˜as et al 61 The results of these experiments are as follows:…”
Section: Ar-qr Code Applicationmentioning
confidence: 74%
“…The UI is controlled by hand gestures and voice commands making the application more intuitive and immersive. This application has been successfully demonstrated in a smart inspection of a nuclear facility in previous research by the same authors Mascaren˜as et al 61 The results of these experiments are as follows:…”
Section: Ar-qr Code Applicationmentioning
confidence: 74%
“…Ahn et al (2019) proposed a two-step method, including image segmentation for filtering out the markers and object detection for estimating the coordinates, to perform geometric transformation for projection-based display. Mascareñas et al (2019) adopted various types of markers (e.g., barcode, QR code) in order to cope with the common occurrence of facilities in nuclear infrastructure. Although marker-based methods are relatively straightforward to use, they require markers being placed at suitable locations without any occlusions.…”
Section: Resultsmentioning
confidence: 99%
“…However, only three recent studies reported success cases of hybrid interaction in construction. In these studies, users were asked to wear the head-mounted device (i.e., Microsoft HoloLens) and interact with the virtual contents by their gestures (Baek et al , 2019; Mascareñas et al , 2019). Despite the diverse interaction mechanisms, no study has used speech or eye movement as inputs for intuitive interaction, leaving a possibility for further investigation.…”
Section: Resultsmentioning
confidence: 99%
“…Virtual reality (VR) refers to computer technologies and interfaces to simulate a 3D and interactive environment; whereas, augmented reality (AR) implies layering virtual information on real-world objects. 343 Initially inspired and developed for the gaming community, VR and AR are now finding their way into other fields, such as nuclear facilities 344 or medical fields. 345 In SHM systems, such novel approaches are becoming a trend.…”
Section: Virtual Reality and Augmented Reality For Shmmentioning
confidence: 99%